2001
DOI: 10.1021/bi011067h
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Bloom's and Werner's Syndrome Helicases by G-Quadruplex Interacting Ligands

Abstract: G-Quadruplex DNAs are folded, non-Watson-Crick structures that can form within guanine-rich DNA sequences such as telomeric repeats. Previous studies have identified a series of trisubstituted acridine derivatives that are potent and selective ligands for G-quadruplex DNA. These ligands have been shown previously to inhibit the activity of telomerase, the specialized reverse transcriptase that regulates telomere length. The RecQ family of DNA helicases, which includes the Bloom's (BLM) and Werner's (WRN) syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 58 publications
1
73
0
1
Order By: Relevance
“…These molecules preferentially localize and act at telomeres. They inhibit the activity of canonical DNA polymerases (24) and helicases (25,26) on telomeric substrates and delocalize telomeric proteins from telomeres (27), which, together with their effects on telomerase activity, participate to their selective cytotoxicity toward cancer cells and their efficiency as anticancer drugs. Telomerase is one of the enzymes that must be evaluated in the design and development of new G-quadruplex ligands, and we provide here an approach to validate carefully such candidates.…”
Section: Mechanisms Of Action Of G-quadruplex Ligandsmentioning
confidence: 99%
“…These molecules preferentially localize and act at telomeres. They inhibit the activity of canonical DNA polymerases (24) and helicases (25,26) on telomeric substrates and delocalize telomeric proteins from telomeres (27), which, together with their effects on telomerase activity, participate to their selective cytotoxicity toward cancer cells and their efficiency as anticancer drugs. Telomerase is one of the enzymes that must be evaluated in the design and development of new G-quadruplex ligands, and we provide here an approach to validate carefully such candidates.…”
Section: Mechanisms Of Action Of G-quadruplex Ligandsmentioning
confidence: 99%
“…We therefore examined whether WRN was involved in the CRS assay. As an initial approach, we performed the CRS assay in the presence of a specific inhibitor (tetra-N-methylpyridylporphin) of RecQ helicases (61) and found that this drug was strongly inhibitory (Fig. 6A).…”
Section: The Pso4 Complex Is Required For In Vitro Processing Of Icls-tomentioning
confidence: 99%
“…These structures could make the damaged D-loops the preferred substrates for BLM and WRN helicase activity. One of the possible structures could be G-quadruplex (G4) formation, as both BLM and WRN work particularly efficiently on these structures (33). Szalai et al (46) reported the formation of G-quadruplex and other secondary structures upon conversion of guanine to 8-oxodG in telomeric DNA in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This result clearly demonstrates that there is no contaminating glycosylase activity in the proteins used in this study. (33,34) and have been implicated in DNA repair (12,15,16). On the other hand, the role of RecQ5 is not clear yet (35).…”
Section: Construction Of D-loops With and Without The 8-oxodgmentioning
confidence: 99%